Method for electric pulse recovery of cold deformed pearlitic steel and pearlitic steel

CN123005083APending Publication Date: 2026-10-30NORTHEASTERN UNIV CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611500358.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]有鉴于此,本申请旨在提供一种冷变形珠光体钢的电脉冲恢复方法和珠光体钢,解决现有技术难以兼顾扭转剪切损伤珠光体钢抗拉强度恢复与塑性改善的问题

Benefits of technology

本申请提供的电脉冲恢复方法,通过第一脉冲处理激活位错运动并实现初步重排,之后中断高温暴露并锁定重排后的位错组态,接着再次进行第二脉冲处理,在保留第一次脉冲处理位错初步重排的基础上进行二次调控,最终冷却使优化后的微观结构稳定定型,即通过两次脉冲处理之间的间歇冷却,在保留足够脉冲作用次数的同时缩短材料在预设温度附近的连续暴露时间,从而在实现位错结构有效重排和均匀化的前提下,避免渗碳体片层球化和强度损失,兼顾抗拉强度的恢复与塑性的改善。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123005083A_ABST
    Figure CN123005083A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of damage recovery treatment of high-strength metal materials, and provides an electric pulse recovery method of cold-deformed pearlitic steel and the pearlitic steel. The pearlitic steel is obtained through cold drawing and twisting. The electric pulse recovery method of the cold-deformed pearlitic steel comprises the following steps: forming an electric conduction loop between the pearlitic steel and an electric pulse device; performing first pulse treatment on a to-be-treated area of the pearlitic steel, so that the surface temperature of the to-be-treated area is increased to a preset temperature, and the preset temperature is 290 DEG C to 310 DEG C; performing cooling treatment on the pearlitic steel after the first pulse treatment until the ambient temperature; performing second pulse treatment on the to-be-treated area of the pearlitic steel, so that the surface temperature of the to-be-treated area reaches the preset temperature; and performing cooling treatment on the pearlitic steel after the second pulse treatment until the ambient temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of damage recovery technology for high-strength metallic materials, and in particular to an electrical pulse recovery method for cold-deformed pearlitic steel and the pearlitic steel itself. Background Technology

[0002] High-carbon pearlitic steel, after multiple cold drawing processes, is widely used in high-strength load-bearing wires such as bridge cables and steel ropes. During subsequent twisting, turning, or assembly processes, cold-drawn steel wires undergo additional shear deformation, causing pearlite lamellar deflection, uneven local strain, and damage accumulation, resulting in a decrease in tensile strength, maximum uniform strain, and fracture strain.

[0003] Currently, low-temperature heat treatment and other methods are commonly used in production to improve the residual stress state and mechanical properties of cold-drawn steel wire. However, existing processing techniques mainly target the microstructure and stress state formed during the cold drawing process. Their improvement effect on dislocation accumulation, local stress concentration and plastic degradation caused by subsequent torsional shear deformation is still relatively limited. Summary of the Invention

[0004] In view of this, this application aims to provide an electrical pulse recovery method for cold-deformed pearlitic steel and pearlitic steel, solving the problem that the prior art is unable to simultaneously achieve the recovery of tensile strength and improvement of plasticity in pearlitic steel damaged by torsion and shear.

[0005] In a first aspect, this application provides an electrical pulse recovery method for cold-deformed pearlitic steel, wherein the pearlitic steel is obtained by torsion after cold drawing, and the electrical pulse recovery method includes: Controlling the formation of a conductive circuit between pearlitic steel and electrical pulse equipment; The pearlitic steel is subjected to a first pulse treatment to raise the surface temperature of the area to be treated to a preset temperature of 290℃~310℃. The pearlitic steel treated with the first pulse was cooled to ambient temperature. The pearlitic steel is subjected to a second pulse treatment to bring the surface temperature of the area to be treated to the preset temperature. The pearlitic steel treated with the second pulse was cooled to ambient temperature.

[0006] In some implementations, the processing time t1 of the first pulse processing and the processing time t2 of the second pulse processing satisfy t1≤t2.

[0007] In some implementations, the processing time t1 of the first pulse is 25s≤t1≤30s.

[0008] In some implementations, the processing time t2 of the second pulse is 30s ≤ t2 ≤ 120s.

[0009] In some implementations, during the second pulse processing, the surface temperature of the area to be processed is kept in dynamic thermal equilibrium within the range of 295°C to 305°C.

[0010] In some embodiments, the electrical processing parameters of the first pulse processing include: a first peak current density of 800-850 A / mm², a first single pulse width of 30 μs, and a first frequency of 35 Hz.

[0011] In some embodiments, the electrical processing parameters for the second pulse processing include: a second peak current density of 800–850 A / mm², a second single pulse width of 30 μs, and a second frequency of 35 Hz.

[0012] In some implementations, at least one of the first pulse processing and the second pulse processing is a unidirectional square wave pulse.

[0013] In some implementations, the electrical processing parameters of the first pulse processing are the same as those of the second pulse processing.

[0014] In some embodiments, the electrical pulse recovery method further includes, prior to the step of controlling the formation of a conductive circuit between the pearlitic steel and the electrical pulse device: Pearlitic steel undergoes multi-stage grinding, cleaning, and drying.

[0015] Secondly, this application provides a pearlitic steel prepared by the electrical pulse recovery method for cold-deformed pearlitic steel as provided in any of the above embodiments.

[0016] In some embodiments, the pearlitic steel comprises, by mass percentage, 0.96% C, 1.10% Si, 0.60% Mn, 0.45% Cr, 0.01% P, 0.01% S, 0.18% Ni, with the balance being Fe and unavoidable impurities.

[0017] Compared with the prior art, the beneficial effects of this application are: The electrical pulse recovery method provided in this application activates dislocation movement and achieves preliminary rearrangement through a first pulse treatment. Then, the high-temperature exposure is interrupted and the rearranged dislocation configuration is locked. Next, a second pulse treatment is performed. Based on the preliminary dislocation rearrangement of the first pulse treatment, secondary regulation is carried out. Finally, cooling is performed to stabilize and shape the optimized microstructure. That is, through intermittent cooling between the two pulse treatments, the continuous exposure time of the material near the preset temperature is shortened while retaining a sufficient number of pulse treatments. Thus, under the premise of achieving effective rearrangement and homogenization of dislocation structure, cementite lamellar spheroidization and strength loss are avoided, and the recovery of tensile strength and improvement of plasticity are taken into account.

[0018] In other words, cold drawing followed by torsion introduces high-density entangled dislocations and localized strain concentrations into pearlitic steel, leading to a synergistic decrease in strength and plasticity. This application addresses this by first heating the material to a preset temperature using a pulse treatment, which activates dislocation clusters to untangle and rearrange, releasing localized stress concentrations. Intermittent cooling to ambient temperature interrupts continuous high-temperature exposure, preventing cementite lamellar spheroidization and excessive recovery. A second pulse treatment raises the temperature back to the same preset temperature, further homogenizing the remaining dislocation structure and promoting a more uniform dislocation distribution. A cooling step is inserted between the two pulse treatments, allowing the beneficial effects of dislocation rearrangement to be achieved in stages while controlling the cumulative effect of high temperatures.

[0019] The electrical pulse recovery method provided in this application divides the total pulse train time into two stages and sets a cooling step in between. While realizing dislocation rearrangement and residual stress release, it effectively controls the continuous exposure time of the material in the high-temperature region, avoids significant spheroidization of cementite lamellars and strength loss caused by excessive recovery, and restores the tensile strength of torsional shear damaged pearlitic steel. The maximum uniform strain and fracture strain are significantly improved, and the synergistic improvement of strength and plasticity is achieved.

[0020] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 A flowchart of the electrical pulse recovery method provided in the embodiments of this application; Figure 2 A schematic diagram of the pulse train on / off timing and temperature change path of the electrical pulse provided in the embodiments of this application; Figure 3 The tensile fracture morphology of the torsional shear damaged material provided in the embodiments of this application is shown in (a) and (b) respectively. Figure 4 The tensile fracture morphology of Embodiment 2 of this application is shown, wherein (a) is a low magnification view and (b) is a high magnification view; Figure 5 Scanning electron microscopy morphology of pearlite lamellar material in torsional shear damage state; Figure 6The morphology of pearlite sheets after electrical pulse processing provided in Embodiment 2 of this application is shown in the scanning electron microscope. Figure 7 The images shown are representative transmission electron microscope images of the materials under different conditions, where (a) is the torsional shear damage state; (b) is the state treated with a continuous electrical pulse for 90 s; and (c) is the state treated with an electrical pulse in Example 2. Detailed Implementation

[0023] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0024] Firstly, this application provides an electrical pulse recovery method for cold-deformed pearlitic steel, which is obtained by torsion after cold drawing. Cold deformation includes cold drawing and torsional shearing. During cold drawing, the pearlitic steel forms a pearlitic lamellar structure arranged along the drawing direction, and high-density dislocations accumulate in the ferrite matrix, resulting in work hardening. On this basis, room temperature torsional deformation is applied, subjecting the material to additional shear stress components. The pearlitic lamellae deflect and bend, and strain concentration occurs in local areas. The dislocation structure becomes further complex, forming entangled dislocation clusters and local dislocation walls. A composite damage state is formed during cold drawing and torsional shearing, which leads to a decrease in the dislocation mobility of the material. During deformation, dislocations are difficult to initiate and slip under low stress, resulting in a decrease in tensile strength, reduced uniform deformation capacity, and decreased fracture strain.

[0025] Among them, such as Figure 1 and Figure 2 As shown, the electrical pulse recovery method includes: S102 controls the formation of a conductive circuit between the pearlitic steel and the electrical pulse device.

[0026] Pearlitic steel serves as the conductive medium. Its two ends are electrically connected to the power supply of the electrical pulse device via conductive clamps, allowing pulse current to flow through the area of ​​the pearlitic steel to be treated. This generates Joule heating and electroplastic effects, ensuring the pulse current flows stably through the treated area according to preset parameters. The stability of the conductive circuit directly affects the waveform quality of the pulse current and the consistency of energy input, which is fundamental to ensuring the repeatability of subsequent pulse processing results.

[0027] S104, the pearlitic steel area to be treated is subjected to the first pulse treatment, so that the surface temperature of the area to be treated is raised to the preset temperature.

[0028] The area to be treated refers to the specific section of pearlitic steel that needs to undergo performance restoration. In a specific implementation, the pearlitic steel is a conductive unit, and the parallel section of the conductive unit is the area to be treated. The parallel section corresponds to the section where the strain state is relatively uniform after torsional shear deformation.

[0029] Specifically, the conductive unit is taken from a high-carbon pearlitic steel wire that has undergone multiple cold drawing processes and then unidirectional torsional shear deformation at room temperature to form a shear damage state. The high-carbon pearlitic steel has a lamellar pearlitic structure, and the length direction of the parallel section of the conductive unit is parallel to the axis of the steel wire. The nominal engineering shear strain is calculated according to γ=2πNr / L, where N is the number of torsion turns, r is the distance from the center of the parallel section to the axis of the steel wire, and L is the effective torsional length.

[0030] In one specific embodiment, with N=31, r=1.75 mm, and L=700 mm, the nominal engineering shear strain at the center of the cross-section is approximately 0.487, the length of the parallel section is 15.00 mm, and the initial minimum conductive cross-sectional area of ​​the parallel section is 2.40 mm². The first pulse treatment refers to the initial application of an electrical pulse to the region to be treated. This pulse rapidly raises the temperature of the region through the Joule heating effect of the pulse current, while simultaneously promoting dislocation movement using the non-thermal effects of the pulse current.

[0031] Specifically, when the pulsed current flows through the region to be treated, a Joule heating effect is generated inside the material, causing the temperature to rise rapidly to the preset temperature. At the same time, the non-thermal effects accompanying the pulsed current directly act on the dislocation structure. Driven by the synergistic effect of thermal activation energy and electron wind, the high-density entangled dislocation clusters introduced by cold drawing and torsion gain sufficient energy to overcome their pinning effects, resulting in untangling, climb, and cross-slip. This initially releases the local stress concentration. This step is used to activate the material from a high-energy damaged state to a dislocation-mobile state, establishing a structural basis for subsequent rearrangement.

[0032] S106, the pearlitic steel treated with the first pulse is cooled to ambient temperature.

[0033] After the first pulse treatment is completed, the pulse output is stopped, and the pearlitic steel is kept in a clamped state to allow natural heat dissipation until the surface temperature of the area to be treated drops to near the ambient temperature, which is approximately 20℃~40℃.

[0034] After the pulse output is stopped, the material dissipates heat naturally while remaining clamped, and the surface temperature drops from the preset temperature to near ambient temperature. This step interrupts the material's high-temperature thermal exposure near the preset temperature, freezing the rearranged dislocation structures at low temperatures and preventing dislocation degree recovery and significant spheroidization of cementite lamellars caused by sustained high temperatures. Simultaneously, cooling to ambient temperature resets the material's thermal history, providing a similar starting temperature for the second pulse treatment as the first, thus significantly shortening the cumulative high-temperature exposure time while maintaining the same theoretical number of pulses.

[0035] S108, the pearlitic steel area to be treated is subjected to a second pulse treatment, so that the surface temperature of the area to be treated reaches the preset temperature.

[0036] The second pulse treatment refers to the process of applying a pulsed current to the same area to be treated again after cooling to ambient temperature. The second pulse treatment brings the temperature of the pearlitic steel back to the same preset temperature at the end of the first pulse treatment, that is, applying a second electrical pulse to the pearlitic steel under similar temperature conditions, giving dislocations the opportunity for secondary rearrangement and further homogenization.

[0037] After the initial dislocation rearrangement has been achieved through the first pulse treatment, a second pulse current is applied to raise the temperature back to the preset level. Since some tangled dislocations have been untangled and rearranged after the first treatment, the dislocation configuration of the material is more uniform than in the initial state. At this time, the thermal activation in the second pulse treatment allows the remaining dislocation structure to have the opportunity for further rearrangement and adjustment, promoting a more uniform dislocation distribution, reducing the number of large-scale dislocation clusters or entanglements, and further deepening the regulatory effect of pulse treatment on the dislocation structure, thereby achieving a better strong-plasticity match.

[0038] S110, the pearlitic steel treated with the second pulse is cooled to ambient temperature.

[0039] After the second pulse treatment is completed, the pulse output is stopped again, allowing the pearlitic steel to cool naturally to room temperature, thus completing the entire recovery process. The dislocation structure, which has been adjusted to a uniform distribution state after two pulse treatments, is stably retained inside the material during the cooling process, while the material temperature is restored to room temperature, which is convenient for subsequent performance testing or direct use.

[0040] The electrical pulse recovery method provided in this application activates dislocation movement and achieves preliminary rearrangement through a first pulse treatment. Then, the high-temperature exposure is interrupted and the rearranged dislocation configuration is locked. Next, a second pulse treatment is performed. Based on the preliminary dislocation rearrangement of the first pulse treatment, secondary regulation is carried out. Finally, cooling is performed to stabilize and shape the optimized microstructure. That is, through intermittent cooling between the two pulse treatments, the continuous exposure time of the material near the preset temperature is shortened while retaining a sufficient number of pulse treatments. Thus, under the premise of achieving effective rearrangement and homogenization of dislocation structure, cementite lamellar spheroidization and strength loss are avoided, and the recovery of tensile strength and improvement of plasticity are taken into account.

[0041] In other words, cold drawing followed by torsion introduces high-density entangled dislocations and localized strain concentrations into pearlitic steel, leading to a synergistic decrease in strength and plasticity. This application addresses this by first heating the material to a preset temperature using a pulse treatment, which activates dislocation clusters to untangle and rearrange, releasing localized stress concentrations. Intermittent cooling to ambient temperature interrupts continuous high-temperature exposure, preventing cementite lamellar spheroidization and excessive recovery. A second pulse treatment raises the temperature back to the same preset temperature, further homogenizing the remaining dislocation structure and promoting a more uniform dislocation distribution. A cooling step is inserted between the two pulse treatments, allowing the beneficial effects of dislocation rearrangement to be achieved in stages while controlling the cumulative effect of high temperatures.

[0042] The electrical pulse recovery method provided in this application divides the total pulse train time into two stages and sets a cooling step in between. While realizing dislocation rearrangement and residual stress release, it effectively controls the continuous exposure time of the material in the high-temperature region, avoids significant spheroidization of cementite lamellars and strength loss caused by excessive recovery, and restores the tensile strength of torsional shear damaged pearlitic steel. The maximum uniform strain and fracture strain are significantly improved, and the synergistic improvement of strength and plasticity is achieved.

[0043] In some implementations, the preset temperature is 290°C to 310°C.

[0044] The tangled dislocation clusters formed by cold drawing and twisting require sufficiently high temperatures to obtain the activation energy needed to overcome the interaction forces between dislocations.

[0045] In this embodiment, the preset temperature is limited to 290℃~310℃, which constitutes the optimal temperature window. This temperature range ensures that the tangled dislocation clusters obtain sufficient thermal activation energy to achieve untangling and rearrangement, while controlling the high temperature conditions within the safe boundary of the cementite lamellars not significantly spheroidizing. Thus, while restoring tensile strength and improving plasticity, irreversible softening damage to the pearlite structure due to excessive temperature is avoided.

[0046] In some implementations, the processing time t1 of the first pulse processing and the processing time t2 of the second pulse processing satisfy t1≤t2.

[0047] Processing time refers to the duration of time during a single pulse processing, when the pulse current is continuously applied to the area to be processed, measured in seconds (s).

[0048] Where t1 is the duration of the first pulse processing from the start of power-on to the stop of pulse output, and t2 is the duration of the second pulse processing.

[0049] The first pulse treatment involves rapidly heating the material from room temperature to a preset temperature, causing the entangled dislocation clusters to acquire initial thermal activation energy and undergo preliminary untangling and rearrangement. The processing time of the first pulse treatment is mainly determined by the time required to heat to the preset temperature.

[0050] The second pulse treatment involves heating the material to a preset temperature again after it has cooled to ambient temperature. Its function includes not only secondary heating but also maintaining the preset temperature for a certain period of time to further homogenize the dislocation structure and fully release residual stress.

[0051] In this embodiment, by limiting the duration of the second pulse processing to be no less than that of the first pulse processing, it is ensured that the second pulse processing has sufficient time to fully regulate the dislocation structure at a preset temperature, so that the remaining dislocations after the initial rearrangement by the first pulse processing have a further opportunity to be homogenized.

[0052] In some implementations, the processing duration t1 of the first pulse is 25s ≤ t1 ≤ 30s. Optionally, t1 can be 25s, 26s, 27s, 28s, 29s, or 30s.

[0053] In some implementations, the processing duration t2 of the second pulse is 30s ≤ t2 ≤ 120s. Optionally, t2 can be 30s, 32s, 34s, 36s, 38s, 40s, 42s, 44s, 46s, 48s, 50s, 60s, 70s, 80s, 90s, 100s, 110s, or 120s.

[0054] In this embodiment, by limiting t1 to 25s–30s and t2 to 30s–120s, specific and operable process parameter ranges are provided for the processing time of the two stages. The duration range of t1 ensures that the first pulse processing completes the heating to the preset temperature and achieves initial dislocation activation in the shortest possible time, avoiding unnecessary heat accumulation. The duration range of t2 ensures that the second pulse processing has sufficient additional time to fully regulate the dislocation structure at the preset temperature after completing the heating, while keeping the heat exposure within safe boundaries.

[0055] In some implementations, during the second pulse processing, the surface temperature of the area to be processed is kept in dynamic thermal equilibrium within the range of 295°C to 305°C.

[0056] As the second pulse treatment continues, Joule heat generated by the pulsed current accumulates within the material, causing the temperature to gradually rise. As the temperature increases, the temperature difference between the material and the environment widens, leading to a corresponding increase in the heat dissipation rate. When the heat dissipation rate equals the Joule heat generation rate, the material temperature stops rising, entering a state of dynamic thermal equilibrium.

[0057] At an equilibrium temperature of 295℃ to 305℃, dislocations continuously acquire thermal activation energy for climb and rearrangement. Simultaneously, this temperature remains within a safe window where significant spheroidization of the cementite lamellars does not occur. The existence of this dynamic thermal equilibrium state means that, under fixed pulse parameters, the material can be stably maintained within the optimal processing temperature range for an extended period without concern about the temperature continuously rising beyond the safe boundary. This dynamic thermal equilibrium state provides stable temperature conditions for the full control of the second pulse treatment, allowing the dislocation structure to fully rearrange and homogenize under isothermal conditions. The dynamic thermal equilibrium state avoids the risk of cementite lamellar spheroidization that may be caused by continuous temperature increases, while also allowing operators to maintain a stable processing temperature without real-time adjustment of electrical parameters during pulse treatment, thus improving the operability of the process and the consistency of the treatment effect.

[0058] In some embodiments, the electrical processing parameters of the first pulse processing include: a first peak current density of 800-850 A / mm², a first single pulse width of 30 μs, and a first frequency of 35 Hz.

[0059] In some embodiments, the electrical processing parameters for the second pulse processing include: a second peak current density of 800–850 A / mm², a second single pulse width of 30 μs, and a second frequency of 35 Hz.

[0060] The peak current density refers to the ratio of the peak current value of the pulse to the conductive cross-sectional area of ​​the region to be processed, measured in amperes per square millimeter (A / mm²). The pulse width refers to the duration of each pulse, which is 30 μs. The frequency refers to the number of pulses per unit time (per second), which is 35 Hz. These electrical processing parameters collectively determine the Joule thermal power and total energy input to the region to be processed per unit time.

[0061] In this embodiment, the combination of peak current density of 800-850 A / mm², single pulse width of 30 μs, and frequency of 35 Hz determines the Joule thermal power density of the pulse current, P = J²·ρ·τ·f, where J is the peak current density, ρ is the resistivity, τ is the single pulse width, and f is the frequency.

[0062] Under the combination of the above electrical treatment parameters, the area to be treated receives sufficient heat input within t1 and t2 to raise its surface temperature from the ambient temperature to the preset temperature.

[0063] Specifically, for peak current density, a lower limit of 800 A / mm² ensures sufficient heat input to complete heating within 30 seconds, while an upper limit of 850 A / mm² prevents excessively high heat input from causing rapid heating, difficulty in temperature control, or exceeding the critical temperature for cementite spheroidization. A short pulse width of 30 μs facilitates the use of the non-thermal effects of the pulsed current to promote dislocation movement, while avoiding the sustained heating effect caused by excessively long single pulse durations. A frequency of 35 Hz achieves a balance between pulse interval and heat accumulation, resulting in a uniform temperature rise rather than drastic fluctuations.

[0064] In one specific implementation, the peak current density is calculated as the ratio of the pulse peak current to the initial minimum conductive cross-sectional area of ​​the parallel segment of the conductive unit. Here, the pulse peak current is approximately 2000 A, the initial minimum conductive cross-sectional area of ​​the parallel segment is 2.40 mm², and the corresponding peak current density is approximately 833 A / mm².

[0065] In some implementations, at least one of the first pulse processing and the second pulse processing is a unidirectional square wave pulse.

[0066] A unidirectional square wave pulse is a square wave pulse whose current direction remains consistent and whose waveform is rectangular. The unidirectional square wave pulse provides a stable current direction and a constant peak current, facilitating the acquisition of predictable Joule thermal and non-thermal effects.

[0067] In some implementations, the electrical processing parameters of the first pulse processing are the same as those of the second pulse processing, that is, the peak pulse current, pulse width, frequency and waveform of the two stages are the same, and the theoretical number of pulses is determined by the processing time.

[0068] This embodiment simplifies process operation and equipment setup by making the electrical treatment parameters identical in both stages. Operators no longer need to switch electrical parameters between the two stages, reducing process complexity and the risk of human error. Simultaneously, identical electrical parameters enhance the comparability of the treatment effects between the two stages, facilitating precise control of the treatment degree by adjusting the duration rather than the electrical parameters.

[0069] In some embodiments, the electrical pulse recovery method further includes, prior to the step of controlling the formation of a conductive circuit between the pearlitic steel and the electrical pulse device: Pearlitic steel undergoes multi-stage grinding, cleaning, and drying.

[0070] Multi-stage grinding refers to the process of sequentially grinding the surface of pearlitic steel material with sandpaper of different grit sizes. In one specific embodiment, multi-stage grinding includes sequentially grinding with 400#, 1000#, 1500# and 2000# sandpaper.

[0071] Cleaning and drying refers to cleaning the polished material with anhydrous ethanol to remove surface contaminants and residual abrasive particles, followed by drying.

[0072] In this embodiment, multi-stage grinding and cleaning / drying processes are performed on the pearlitic steel to remove the processing-affected layer and contaminants from the material surface, reducing surface roughness and ensuring a stable, uniform, and low-resistance electrical contact between the area to be treated and the conductive fixture. This pretreatment step allows the pulse current to flow uniformly through the area to be treated according to preset parameters, avoiding uneven current distribution and local overheating caused by poor contact or differences in surface conditions. This improves the repeatability and consistency of the electrical pulse treatment effect and provides a reliable surface foundation for the stable implementation of the two-stage intermittent electrical pulse recovery method.

[0073] One specific embodiment of this application uses B96SiQL high-carbon pearlitic steel hot-rolled wire rod as raw material. Its measured chemical composition is shown in Table 1, with the balance being Fe and unavoidable impurities.

[0074] Table 1 Chemical composition (mass fraction, %) of the materials in the examples

[0075] Hot-rolled wire rod with a diameter of 14.5 mm was cold-drawn to a diameter of 7.0 mm in eight passes, with a total area true strain of approximately 1.456 and a total area compression ratio of approximately 76.7%. The cold-drawn wire was then subjected to unidirectional torsion at room temperature, with an effective torsion length of 700 mm, 31 turns, a torsion speed of 360° / min, and an axial tension of 70 N. After torsion and cooling to room temperature, conductive units were obtained by wire electrical discharge machining (EDM).

[0076] The center of the parallel segment of the conductive unit is located approximately 1.75 mm from the axis of the steel wire, where the nominal engineering shear strain is approximately 0.487. The parallel segment of the conductive unit has a length of 15.00 mm, a width of 2.00 mm, a thickness of 1.20 mm, a transition arc radius of R8, a total length of 32.00 mm, and an initial minimum conductive cross-sectional area of ​​2.40 mm².

[0077] Another cold-drawn steel wire, which had undergone the above eight cold-drawing processes to a diameter of 7.0 mm and had not been twisted, was used as the reference material in the drawn state. The sampling location, sampling direction, specimen size, surface treatment method, and tensile test conditions of the drawn state specimen were the same as those of the torsional shear damage specimen. The only difference between the two was that the drawn state reference material had not undergone torsional shear deformation.

[0078] During the electrical pulse processing, a pure copper clamp with good conductivity is used to hold both ends of the material, and a K-type thermocouple with a wire diameter of 0.3 mm and a TES-1310 digital temperature gauge are used to monitor the surface temperature of the middle section of the parallel segment of the material; the temperature gauge reads at a frequency of 2.5 times / s. Temperature measurement accuracy within the range of 50–1000 ℃ is ±(0.3% of reading + 1 ℃), and calibration must be performed before use. Tensile property tests are conducted at room temperature with a tensile speed of 0.5 mm / min. Three parallel samples are tested for each condition, and results are expressed as mean ± sample standard deviation.

[0079] Example 1 Using the above-mentioned cold-drawn pearlitic steel wire in the torsional shear damage state, conductive units were obtained from approximately 1.75 mm from the wire axis using wire electrical discharge machining (EDM), and the following experiments were conducted: (1) Sample pretreatment: Take a material unit with a parallel section length of 15.00 mm, width of 2.00 mm, thickness of 1.20 mm, and minimum conductive cross-sectional area of ​​2.40 mm². Grind it step by step with 400#, 1000#, 1500# and 2000# sandpaper to remove the surface processing layer. Then clean it with anhydrous ethanol and dry it to ensure stable contact with the conductive fixture. (2) First pulse treatment: A unidirectional square wave pulse with a peak current of about 2000 A, a peak current density of about 833 A / mm², a single pulse width of 30 μs, and a frequency of 35 Hz was used to treat the material surface for 30 s, so that the surface temperature of the material increased from about 30 ℃ to about 300 ℃. Representative temperature records show that the surface temperature at the end of the first pulse treatment was about 290 ℃. (3) Interstage cooling: Stop the pulse output and allow the material to cool naturally to near ambient temperature while holding it in a pure copper clamp. Under the sample size and environmental conditions of this embodiment, the cooling time is about 20 seconds and the material surface temperature drops to close to 30°C. (4) Second pulse treatment: The same electrical pulse parameters as the first pulse treatment are used to treat the material again for 30 s, so that the surface temperature of the material rises again to about 300 ℃. Then the pulse output is stopped and the material is allowed to cool naturally to room temperature. The total pulse train time for the two stages is 60 s.

[0080] Room temperature tensile tests were conducted on the pull-out reference material, the torsional shear damaged material, and the material treated in this embodiment. The results are shown in Table 2.

[0081] Table 2 Tensile properties of materials under pull-out, torsional shear damage, and treatment in Example 1.

[0082] Compared with the torsional shear damage state, the ultimate tensile strength of the material treated in Example 1 increased by about 6.5%, the maximum uniform strain increased by about 71.3%, and the fracture strain increased by about 46.8%, indicating that the two-stage treatment with a total pulse train time of 60 s can significantly improve the uniform deformation capacity and fracture plasticity while restoring the tensile strength.

[0083] Example 2 Using the same torsional shear-damaged cold-drawn pearlitic steel material as in Example 1, conductive units of the same size were obtained by wire electrical discharge machining, and the following experiments were conducted: (1) Sample pretreatment: The surface of the material unit was polished step by step with 400#, 1000#, 1500# and 2000# sandpaper, cleaned with anhydrous ethanol and dried, and then the two ends of the material were clamped with pure copper clamps. (2) First pulse treatment: A unidirectional square wave pulse with a peak current of about 2000 A, a peak current density of about 833 A / mm², a single pulse width of 30 μs, and a frequency of 35 Hz was used to treat the material surface for 30 s, so that the surface temperature of the material increased from about 30 ℃ to about 300 ℃. Representative temperature records show that the surface temperature at the end of the first pulse treatment was about 290 ℃. (3) Inter-stage cooling: Stop the pulse output and allow the device to cool naturally to near ambient temperature while maintaining the pure copper clamp. Under the conditions of this embodiment, the cooling time is approximately 20 seconds. (4) Second pulse treatment: The same electrical pulse parameters as the first pulse treatment are used for another 60 s. For the first 30 s, the surface temperature of the material is raised again to about 300 ℃. After that, for about 30 s, the surface temperature reaches dynamic thermal equilibrium and fluctuates in the range of 295 to 305 ℃ under fixed pulse parameters. Then the pulse output is stopped and the material is allowed to cool naturally to room temperature. The total pulse train time for the two stages is 90 s.

[0084] Room temperature tensile tests were conducted on the pull-out reference material, the torsional shear damaged material, and the material treated in this embodiment. The results are shown in Table 3.

[0085] Table 3 Tensile properties of materials under pull-out, torsional shear damage, and treatment in Example 2.

[0086] Compared to the torsional shear damage state, the ultimate tensile strength of the material treated in this embodiment is increased by approximately 8.7%, the maximum uniform strain is increased by approximately 177.9%, and the fracture strain is increased by approximately 60.0%. This embodiment achieves the best overall balance of strength and ductility among the three sets of embodiments and is the preferred implementation method.

[0087] The low-magnification and high-magnification fracture surfaces of the material in the torsional shear damage state are shown below. Figure 3In (a) and (b), the corresponding fracture surfaces after processing in this embodiment are shown respectively. Figure 4 (a) and (b). Compared with the torsional shear damage state, the material treated in this embodiment exhibits more obvious macroscopic necking and more extensive dimple-type plastic fracture characteristics, consistent with the increase in its maximum uniform strain and fracture strain.

[0088] Pearlite lamellar morphology of materials in torsional shear damage state, such as Figure 5 As shown, the pearlite lamellar morphology of the material after treatment in this embodiment is as follows. Figure 6 As shown. The microstructure sample was sequentially ground, mechanically polished, and etched with 5% nitric acid alcohol for 8 seconds. Within the observed area, the pearlite lamellar structure of this example was generally maintained, and no obvious large-scale cementite spheroidization was observed, indicating that the improvement in plasticity did not mainly depend on severe spheroidization or significant softening.

[0089] Further transmission electron microscopy (TEM) observations were performed on the material in the torsional shear damage state, the material after 90 s of continuous electrical pulse treatment, and the material after treatment in Example 2. Representative images of the three states are shown below. Figure 7 In (a), (b), and (c), the scale bar is 200 nm.

[0090] Figure 7 In the torsional shear damage state in (a), dense linear dislocation contrast, local dislocation clusters or tangles, and strong strain contrast are visible in the representative region, and the outlines of some lamellae are interrupted or near the interface are relatively blurred. Figure 7 In the 90 s continuous electrical pulse processing state in (b), the dislocation contrast in some regions is reduced, but regions with low dislocation contrast coexist with residual high-density regions, and the regional differences are still quite obvious. Figure 7 In the two-stage treatment state (c), the pearlite lamellae are generally preserved, large-scale dislocation clusters or entanglements are reduced, the contrast distribution of fine linear dislocations is relatively uniform, and the partial lamellar breaks and interface contours are relatively clear. These microstructural characteristics are consistent with the higher tensile strength, maximum uniform strain, and fracture strain exhibited in Example 2 compared to the continuous 90-s electrical pulse treatment, and can serve as supplementary evidence for the improvement of defect distribution and strength-plasticity matching through a two-stage intermittent timing process.

[0091] It should be noted that the contrast of a transmission electron microscope is affected by factors such as crystal orientation, film thickness, and diffraction conditions. ​ This is used for qualitative comparison of representative regions under the same scale, without imposing numerical limits on the absolute dislocation density of each state, nor is the above-mentioned microstructure interpretation used as a limiting condition for the scope of protection of this invention.

[0092] Example 3 Using the same torsional shear-damaged cold-drawn pearlitic steel material as in Example 1, conductive units of the same size were obtained by wire electrical discharge machining, and the following experiments were conducted: (1) Sample pretreatment: The surface of the material unit was polished step by step with 400#, 1000#, 1500# and 2000# sandpaper, cleaned with anhydrous ethanol and dried, and then the two ends of the material were clamped with pure copper clamps. (2) First pulse treatment: A unidirectional square wave pulse with a peak current of about 2000 A, a peak current density of about 833 A / mm², a single pulse width of 30 μs, and a frequency of 35 Hz was used to treat the material surface for 30 s, so that the surface temperature of the material increased from about 30 ℃ to about 300 ℃. Representative temperature records show that the surface temperature at the end of the first pulse treatment was about 290 ℃. (3) Inter-stage cooling: Stop the pulse output and allow the device to cool naturally to near ambient temperature while maintaining the pure copper clamp. Under the conditions of this embodiment, the cooling time is approximately 20 seconds. (4) Second pulse treatment: The same electrical pulse parameters as the first pulse treatment are used for another 120 s. For the first 30 s, the surface temperature of the material is raised again to about 300 ℃. For the next 90 s, the surface temperature reaches dynamic thermal equilibrium and fluctuates within the range of 295 to 305 ℃ under fixed pulse parameters. Then the pulse output is stopped and the material is allowed to cool naturally to room temperature. The total pulse train time for the two stages is 150 s.

[0093] Room temperature tensile tests were conducted on the pull-out reference material, the torsional shear damaged material, and the material treated in this embodiment. The results are shown in Table 4.

[0094] Table 4 Tensile properties of materials under pull-out, torsional shear damage, and treatment in Example 3.

[0095] Compared to the torsional shear damage state, the ultimate tensile strength of the material treated in this embodiment increased by approximately 5.9%, the maximum uniform strain increased by approximately 108.2%, and the fracture strain increased by approximately 42.1%. After the second pulse treatment time was extended to 120 s, the material properties decreased slightly compared to Example 2, but were still significantly better than those of the torsional shear damage state.

[0096] Comparative Example To further evaluate the technical effect of the two-stage intermittent timing sequence, the comparative examples all used the same sample specifications and pretreatment methods as the examples described above.

[0097] (a) Conventional annealing comparison test: The sample was placed in a box-type resistance furnace preheated to 300℃. Comparative Example 1 was kept at 2 min, Comparative Example 2 was kept at 7 min, and Comparative Example 3 was kept at 17 min. After the holding time was completed, the sample was taken out and allowed to cool naturally to room temperature in the air.

[0098] (II) Continuous Electrical Pulse Comparison Test: The material was held at both ends using pure copper clamps to form a stable conductive circuit between the material and the electrical pulse power supply. During the treatment, the same electrical pulse parameters as in the examples were used, and continuous electrical pulses of different durations were applied. The total duration of the continuous electrical pulses in Comparative Example 4 was 60s, in Comparative Example 5 it was 90s, and in Comparative Example 6 it was 150s. The pulse output was not stopped or cooled during the pulse output. After the treatment, the pulse output was stopped, and the material was allowed to cool naturally to room temperature while still being clamped.

[0099] (III) High-energy electrical pulse comparison test: The two ends of the material are clamped with pure copper clamps to form a stable conductive circuit between the material and the electrical pulse power supply. A unidirectional square wave pulse with a peak current of about 3000 A, a peak current density of about 1250 A / mm², a single pulse width of 30 μs, and a frequency of 40 Hz is used to treat the material for 20 s, so that the surface temperature of the material rises to about 450℃. After the treatment, the pulse output is stopped and the material is allowed to cool naturally to room temperature.

[0100] With the total pulse train time being the same, the comparative examples and the embodiments of this application all use the same peak current density, pulse width, and frequency, and the theoretical number of pulses is the same. The tensile properties of each comparative example are shown in Table 5.

[0101] Table 5 Tensile properties of each comparative example (mean ± sample standard deviation, n=3)

[0102] Under the condition of the same total pulse train time, the two-stage processing (Examples 1-3) and the continuous electrical pulse processing (Comparative Examples 4-6) used the same peak current density, single pulse width, and frequency, and the same theoretical number of pulses, with a maximum surface temperature of approximately 300°C. However, they did not have the same temperature-time history. Taking a total pulse train time of 90s as an example, in the representative temperature records, the continuous electrical pulse processing (Comparative Example 5) heated up to around 300°C in the first 30s and then remained around 300°C for about 60s. In Example 2, the pulse output stopped after the first pulse processing for 30s and the device was allowed to cool naturally for about 20s to close to 30°C. The device was heated again about 30s before the second pulse processing, and only remained around 300°C for about 30s after the second pulse processing. Therefore, under the condition that the maximum surface temperature and the theoretical number of pulses were basically the same, Example 2 reduced the continuous residence time around 300°C.

[0103] Example 1 showed improvements in ultimate tensile strength, maximum uniform strain, and fracture strain of approximately 3.1%, 21.9%, and 17.5%, respectively, compared to continuous electrical pulse treatment for 60 s (Comparative Example 4); Example 2 showed improvements of approximately 6.9%, 72.6%, and 44.1%, respectively, compared to continuous electrical pulse treatment for 90 s (Comparative Example 5). These results indicate that the cooling-reheating path formed by stopping the pulse between stages and cooling to near ambient temperature, rather than the treatment intensity determined solely by the highest surface temperature or the theoretical number of pulses, is a crucial process factor for achieving different mechanical property recovery effects.

[0104] In Example 3, the ultimate tensile strength and maximum uniform strain were increased by approximately 2.3% and 16.0%, respectively, compared to the continuous 150s pulse treatment (Comparative Example 6). The fracture strain was close to that of the continuous 150s treatment (Comparative Example 6) but slightly lower by approximately 1.9%. When the second pulse treatment time was extended to 120s, the material's continuous exposure time near approximately 300°C increased, and its performance declined compared to Example 2. Therefore, a longer second pulse treatment time is not necessarily better; a second pulse treatment of 60s (Example 2) yields a better overall balance of strength and plasticity.

[0105] The aforementioned duration dependence is consistent with the previously mentioned possible mechanisms: the beneficial electrical pulse-induced defect rearrangement may gradually saturate as the treatment progresses, while excessive recovery and tissue changes caused by sustained high temperatures will still accumulate. When the total pulse train time is extended to 150 s, the second pulse treatment itself lasts for approximately 90 s at around 300°C, thus diminishing the advantage of the two-stage treatment (Example 3) over the continuous treatment (Comparative Example 6). This explanation is intended to illustrate experimental trends and does not constitute a limitation on the scope of protection of this invention, nor does it exclude the simultaneous action of other electrical pulse-defect coupling mechanisms.

[0106] The highest macroscopic surface temperature of the high-energy electrical pulse treatment (Comparative Example 7) was approximately 450°C, and its ultimate tensile strength decreased to approximately 1642.67 MPa, indicating that excessively high peak temperatures may lead to significant strength loss. Although conventional annealing (Comparative Examples 1-3) can improve some plasticity properties, it is difficult to obtain the synergistic recovery of strength and plasticity shown in Example 2 in a short period of time.

[0107] Secondly, this application provides a pearlitic steel prepared using the electrical pulse recovery method provided in any of the above embodiments.

[0108] The pearlitic steel provided in this application is prepared by the electrical pulse recovery method of any of the above embodiments, and thus possesses all the beneficial effects of the electrical pulse recovery method, so it will not be described in detail here.

[0109] The pearlitic steel provided in this application has a reduced number of large-scale dislocation clusters or entanglements in the ferrite matrix in terms of microstructure, a relatively uniform distribution of dislocation contrast, and the pearlite lamellae remain intact overall without obvious large-scale cementite spheroidization. The mechanical properties corresponding to the above microstructure characteristics are that the tensile strength is restored, the maximum uniform strain and fracture strain are significantly improved, and the synergistic improvement of strength and plasticity is achieved.

[0110] In some embodiments, the pearlitic steel comprises, by mass percentage, 0.96% C, 1.10% Si, 0.60% Mn, 0.45% Cr, 0.01% P, 0.01% S, 0.18% Ni, with the balance being Fe and unavoidable impurities.

[0111] In this embodiment, by limiting the chemical composition of the pearlitic steel, sufficient carbon content is ensured to form a high volume fraction pearlitic structure. The added chromium element improves the thermal stability of the cementite, enabling the material to maintain the structural stability of the pearlitic lamellae during cold drawing, torsion, and subsequent electrical pulse treatment at approximately 300°C. The solid solution strengthening effect of silicon, manganese, and nickel provides matrix strength support for the material, while impurities such as sulfur and phosphorus are controlled at low levels to ensure the plasticity and toughness of the material.

[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. A method for recovering electrical pulses from cold-deformed pearlitic steel, wherein the pearlitic steel is obtained by cold drawing followed by torsion, characterized in that... The electrical pulse recovery method for cold-deformed pearlitic steel includes: Controlling the formation of a conductive circuit between the pearlitic steel and the electrical pulse device; The pearlitic steel is subjected to a first pulse treatment to raise the surface temperature of the area to be treated to a preset temperature, which is 290℃~310℃. The pearlitic steel treated with the first pulse is cooled to ambient temperature. The pearlitic steel is subjected to a second pulse treatment to bring the surface temperature of the area to be treated to the preset temperature. The pearlitic steel treated with the second pulse is then cooled to ambient temperature.

2. The method for electrical pulse recovery of cold-deformed pearlitic steel according to claim 1, characterized in that, The processing time t1 of the first pulse processing and the processing time t2 of the second pulse processing satisfy t1≤t2.

3. The method for electrical pulse recovery of cold-deformed pearlitic steel according to claim 2, characterized in that, The processing time t1 of the first pulse is 25s≤t1≤30s.

4. The method for electrical pulse recovery of cold-deformed pearlitic steel according to claim 2, characterized in that, The processing time t2 of the second pulse is 30s≤t2≤120s.

5. The method for electrical pulse recovery of cold-deformed pearlitic steel according to claim 2, characterized in that, In the second pulse processing, the surface temperature of the area to be processed maintains a dynamic thermal equilibrium within the range of 295℃ to 305℃.

6. The method for electrical pulse recovery of cold-deformed pearlitic steel according to claim 2, characterized in that, The electrical processing parameters of the first pulse processing include: a first peak current density of 800-850 A / mm², a first single pulse width of 30 μs, and a first frequency of 35 Hz; and / or, the electrical processing parameters of the second pulse processing include: a second peak current density of 800-850 A / mm², a second single pulse width of 30 μs, and a second frequency of 35 Hz; and / or, at least one of the first pulse processing and the second pulse processing is a unidirectional square wave pulse.

7. The method for electrical pulse recovery of cold-deformed pearlitic steel according to claim 6, characterized in that, The electrical processing parameters for the first pulse processing are the same as those for the second pulse processing.

8. The method for recovering electrical pulses from cold-deformed pearlitic steel according to any one of claims 1 to 7, characterized in that, Prior to the step of controlling the formation of a conductive circuit between the pearlitic steel and the electrical pulse device, the electrical pulse recovery method for the cold-deformed pearlitic steel further includes: The pearlitic steel is subjected to multi-stage grinding, cleaning and drying processes.

9. A pearlitic steel, characterized in that, Prepared using the electrical pulse recovery method for cold-deformed pearlitic steel as described in any one of claims 1 to 8.

10. The pearlitic steel according to claim 9, characterized in that, The pearlitic steel comprises, by mass percentage, 0.96% C, 1.10% Si, 0.60% Mn, 0.45% Cr, 0.01% P, 0.01% S, 0.18% Ni, with the balance being Fe and unavoidable impurities.